How can simulation games foster theory-practice integration in student teachers? Perspectives on their effects and instructional setting - Kienitz, Anna; Justus Liebig University Giessen (My University, 2025)
Teachers often find that there is a gap between their theoretical knowledge and its practical application in the classroom. One key reason for this so-called theory–practice gap is the limited opportunity to practise applying theory during teacher training. Simulation games show promise in closing this gap because they allow learners to engage with authentic teaching scenarios in which they can practise applying theoretical concepts. Despite their potential, little research has been conducted into the impact of simulation games on student teachers' ability to use theoretical knowledge and the variables linked to their motivation to do so. Furthermore, best practices for their instructional setting remain unclear. This thesis presents the findings of two empirical studies examining the use of a teaching simulation game in different instructional settings. The results of both studies indicate that the effectiveness of learning with a simulation game depends on whether learners engage with it in a way that is productive for achieving the learning goal. Therefore, their instructional context should support processes that lead learners to reach the intended learning goal. Based on these findings, the thesis concludes with theoretical and practical recommendations for the effective design and use of simulation games in teacher education.
Keywords: Serious Game; Simulation; Pädagogische Psychologie; Multimedia; ddc:150